Reduced expression of miRNA-27a modulates cisplatin resistance in bladder cancer by targeting the cystine/glutamate exchanger SLC7A11 - Drayton, Ross M.; Dudziec, Ewa; Peter, Stefan; Bertz, Simone; Hartmann, Arndt; Bryant, Helen E.; Catto, James W. F. (Clinical Cancer Research, 2014)
Resistance to cisplatin-based chemotherapy is a major obstacle to bladder cancer treatment. We aimed to identify microRNAs (miRNA) that are dysregulated in cisplatin-resistant disease, ascertain how these contribute to a drug-resistant phenotype, and how this resistance might be overcome.miRNA expression in paired cisplatin-resistant and -sensitive cell lines was measured. Dysregulated miRNAs were further studied for their ability to mediate resistance. The nature of the cisplatin-resistant phenotype was established by measurement of cisplatin/DNA adducts and intracellular glutathione (GSH). Candidate miRNAs were examined for their ability to (i) mediate resistance and (ii) alter the expression of a candidate target protein (SLC7A11); direct regulation of SLC7A11 was confirmed using a luciferase assay. SLC7A11 protein and mRNA, and miRNA-27a were quantified in patient tumor material.A panel of miRNAs were found to be dysregulated in cisplatin-resistant cells. miRNA-27a was found to target the cystine/glutamate exchanger SLC7A11 and to contribute to cisplatin resistance through modulation of GSH biosynthesis. In patients, SLC7A11 expression was inversely related to miRNA-27a expression, and those tumors with high mRNA expression or high membrane staining for SLC7A11 experienced poorer clinical outcomes. Resistant cell lines were resensitized by restoring miRNA-27a expression or reducing SLC7A11 activity with siRNA or with sulfasalazine.Our findings indicate that miRNA-27a negatively regulates SLC7A11 in cisplatin-resistant bladder cancer, and shows promise as a marker for patients likely to benefit from cisplatin-based chemotherapy. SLC7A11 inhibition with sulfasalazine may be a promising therapeutic approach to the treatment of cisplatin-resistant disease.
EVALuna2:6614